Durability of Bridge Structural Elements - Josef Vican; Peter Kotes (Communications - Scientific letters of the University of Zilina, 2016)
Due to environmental actions evocated by the atmospheric behaviour, the material degradation processes are started. The effects of material deterioration due to corrosion cause the loss of cross-sectional or member resistance, but the limit state method does not directly reflect design and verification allowing for failures caused by this influence. The time-variant loss of steel and reinforced concrete moment cross-sectional resistances were computed respecting specific corrosion models to express the time-dependent approximation function taking into account effects of corrosion degradation. The paper presents the general principles of structural elements design for durability based on the limit state concept and their application in the case of moment cross-sectional resistance respecting the effects of corrosion degradation.